The potential contribution of microplastic pollution by organic fertilizers in agricultural soils of Bangladesh: quantification, characterization, and risk appraisals - Rana, Md. Mishail; Haque, Md. Rashedul; Tasnim, Sikder Sanchita; Rahman, Md. Mostafizur (Frontiers in Environmental Science, 2023)
Although plastics are being recycled worldwide, a significant amount of plastic is still directly exposed to the environment and, in the end, forms MPs particles (<5 mm). Soil is a significant sink for plastic waste. Thus, MPs are considered an emerging threat to terrestrial ecosystems. Among several sources, organic fertilizer can be a potential source of MPs to contaminate agricultural soils. Therefore, it was hypothesized that commercial organic fertilizer acts as a carrier of MPs to the agricultural soils in Bangladesh. Hence, 18 organic fertilizers were collected from different local markets of Bangladesh to identify and characterize the potential MPs, like particles following available MPs separation/extraction techniques. Then, a series of experimental steps were conducted, such as microscopic inspection, identification through Fourier Transform-Infra Red Spectroscopy (FT-IR), scanning electron microscopy (SEM), and Energy dispersive X-ray analysis (EDAX). The data were analyzed statistically using both qualitative and quantitative approaches. On average, 1529.62 ± 420.2 MPs items/kg of organic fertilizer were detected in the study, ranging from 433.33 ± 152.75 items/kg to 3466.67 ± 1357.69 items/kg in different organic fertilizers. The size range of 0.5 mm-1.00 mm (30%) was predominant among five different size ranges. The fiber was dominant over various shapes, and seven colours were observed, with black being the most prevalent. Overall, in a year, 971.31-1387.37 particles /m3 area is introduced through organic fertilizer to land. These MPs are further contaminated soil biota and groundwater by their distribution pattern. According to the polymer hazard index (PHI), pollution load index (PLI), and potential ecological risk (PERI), this organic fertilizer belongs to hazard categories III, V, and extreme danger, respectively. This study clearly explained the presence of MPs in commercially available organic fertilizers and their probable effects. This could be applicable in further policy planning to reduce contaminants in formulating organic fertilizers.